Pengaturan Pertanggungjawaban Holding Badan Usaha Milik Negara Sektor Asuransi dan Penjaminan pada Sistem Hukum Nasional di Indonesia - Peacecilia Nonny Suhantri; Jemmy Sondakh; Friend H. Anis (Journal on Education, 2023)
Holding SOE, including SOE holding in the insurance and guarantee sector, is a form of corporate restructuring to improve company performance through the consolidation of several SOE. The holding in the insurance and guarantee sector was formed based on Government Regulation Number 20 of 2020 concerning the Addition of State Equity Participation into the Share Capital of the Company PT Bahana Pembinaan Usaha Indonesia which stipulates PT Bahana Pembinaan Usaha Indonesia as the holding company. The problems in this research are how the legal arrangements for SOEs holding in the insurance and guarantee sector in the national legal system in Indonesia and how the responsibility of the SOEs holding company in the insurance and guarantee sector is for its subsidiaries. Based on the results of the research, it can be seen that the background to the establishment of a SOEs holding company in the insurance and guarantee sector is based on juridical factors, namely in Law Number 19 of 2003 concerning State-Owned Enterprises, Law Number 40 of 2007 concerning Limited Liability Companies, and Government Regulation Number 20 of 2020 concerning the Addition of State Equity Participation into the Share Capital of the Limited Liability Company PT Bahana Pembinaan Usaha Indonesia.